2022
DOI: 10.1177/09673911221109611
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, characterization, and kinetics of N-deacetylation of chitin obtained from mud crab shells

Abstract: This study focuses on the isolation, chemical and crystalline structures, and the kinetics of heterogeneous deacetylation of chitin from mud crab shells ( Scylla serrata). The independent variables in this work are temperature, NaOH concentration, and reaction time. The degree of deacetylation (DD) of the resulting chitosan was determined for different reaction times. It was found that the DD increases nonlinearly with the reaction time. The deacetylation of the chitin followed pseudo first-order kinetics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Data published in the scientific literature [ 3 , 7 ] and our own experimental data [ 44 , 47 , 62 , 63 ] show that α-chitin obtained from various raw materials (crab shells, shrimp, Antarctic krill, as well as the internal organs of crustaceans, for example, the gills of the king crab [ 64 ]), is almost identical both in its chemical composition and in physicochemical properties. A similar conclusion was made in [ 65 ].…”
Section: Kinetics Of the Chitin Deacetylation Reactionsupporting
confidence: 90%
See 3 more Smart Citations
“…Data published in the scientific literature [ 3 , 7 ] and our own experimental data [ 44 , 47 , 62 , 63 ] show that α-chitin obtained from various raw materials (crab shells, shrimp, Antarctic krill, as well as the internal organs of crustaceans, for example, the gills of the king crab [ 64 ]), is almost identical both in its chemical composition and in physicochemical properties. A similar conclusion was made in [ 65 ].…”
Section: Kinetics Of the Chitin Deacetylation Reactionsupporting
confidence: 90%
“…It has been suggested that the presence on the kinetic curve ( Figure 3 ) of areas of fast and slow deacetylation is explained by the presence of amorphous and crystalline [ 80 ] regions in chitin. This hypothesis was put forward in [ 74 ] and continues to be used in various works [ 59 , 65 , 72 ]. It is assumed that in the amorphous regions, the deacetylation reaction proceeds rapidly (the first section of the kinetic curve), while in the crystalline regions, the reaction rate is lower due to the slow diffusion of the reacting particles (alkali molecules or hydroxide ions) to the chitin molecules.…”
Section: Kinetics Of the Chitin Deacetylation Reactionmentioning
confidence: 98%
See 2 more Smart Citations
“…The two discussed peaks suggest that CHSC has the crystalline form of α-chitin, which is typical of marine crustaceans. Contrary to the crab chitin spectrum, the mealworm chitin spectrum in the 1700–1600 cm −1 range has only one distinct peak at 1626 cm −1 indicating a hydrogen bond between the carbonyl groups of amide I and amide II of the same chain [ 21 , 22 ]. This may suggest that a significant part of the chitin coming from the mealworms has the form of β-chitin [ 23 ], typical of the highly elastic structures.…”
Section: Resultsmentioning
confidence: 99%